G6PD and ACSL3 are synthetic lethal partners of NF2 in Schwann cells - Kyrkou, Athena; Valla, Robert; Zhang, Yao; Ambrosi, Giulia; Laier, Stephanie; Müller-Decker, Karin; Boutros, Michael; Teleman, Aurelio A. (Nature Communications, 2024)
Neurofibromatosis Type II (NFII) is a genetic condition caused by loss of the NF2 gene, resulting in activation of the YAP/TAZ pathway and recurrent Schwann cell tumors, as well as meningiomas and ependymomas. Unfortunately, few pharmacological options are available for NFII. Here, we undertake a genome-wide CRISPR/Cas9 screen to search for synthetic-lethal genes that, when inhibited, cause death of NF2 mutant Schwann cells but not NF2 wildtype cells. We identify ACSL3 and G6PD as two synthetic-lethal partners for NF2, both involved in lipid biogenesis and cellular redox. We find that NF2 mutant Schwann cells are more oxidized than control cells, in part due to reduced expression of genes involved in NADPH generation such as ME1. Since G6PD and ME1 redundantly generate cytosolic NADPH, lack of either one is compatible with cell viability, but not down-regulation of both. Since genetic deficiency for G6PD is tolerated in the human population, G6PD could be a good pharmacological target for NFII.